Comparison of energy dissipation in downstream of stepped and baffled spillways of piano key weirs / Comparación de la disipación de energía en aguas abajo de aliviaderos escalonados y desconcertados de vertederos de tecla de piano - Naghib Zadeh, Seyed Mehdi; Heidarnejad, Mohammad; Masjedi, Alireza; Kamanbedast, Amirabbas; Bordbar, Amin (Tecnología y ciencias del agua, 2020)
Heavy seasonal rains over a dam reservoir can lead to huge floods and consequent failure of the dam structure. One way of controlling the adverse effects of heavy rains is to use weirs with larger dimensions such as piano key weirs (PKWs). In spite of raising the overall costs of the project, these weirs are preferred due to their high culvert capacity. PKWs can cause damage to the dam by creating water jets downstream. An effort was made in the present study to examine the energy dissipation due to installation of steps and baffles with different sizes on piano key weirs. The results showed that small baffles and large steps caused maximum energy losses of 85 and 80% in the studied weirs respectively. It was also found that the weir energy dissipation over the spillway was inversely related to its slope angle (the angle between the weir outlet and the vertical wall of the steps/baffles). The other findings were: (1) increasing the flow rate reduced the effect of the steps on the energy loss; (2) the Weber number was directly proportional to the energy loss; and (3) the ratio yc/H (critical depth to the weir head ratio) was directly proportional to the energy loss.